What do warming waters mean for fish physiology and fisheries? - Little, Alexander G.; Loughland, Isabella; Seebacher, Frank (Journal of fish biology, 2020)
Environmental signals act primarily on physiological systems, which then influence higher‐level functions such as movement patterns and population dynamics. Increases in average temperature and temperature variability associated with global climate change are likely to have strong effects on fish physiology and thereby on populations and fisheries. Here we review the principal mechanisms that transduce temperature signals and the physiological responses to those signals in fish. Temperature has a direct, thermodynamic effect on biochemical reaction rates. Nonetheless, plastic responses to longer‐term thermal signals mean that fishes can modulate their acute thermal responses to compensate at least partially for thermodynamic effects. Energetics are particularly relevant for growth and movement, and therefore for fisheries, and temperature can have pronounced effects on energy metabolism. All energy (ATP) production is ultimately linked to mitochondria, and temperature has pronounced effects on mitochondrial efficiency and maximal capacities. Mitochondria are dependent on oxygen as the ultimate electron acceptor so that cardiovascular function and oxygen delivery link environmental inputs with energy metabolism. Growth efficiency, that is the conversion of food into tissue, changes with temperature, and there are indications that warmer water leads to decreased conversion efficiencies. Moreover, movement and migration of fish relies on muscle function, which is partially dependent on ATP production but also on intracellular calcium cycling within the myocyte. Neuroendocrine processes link environmental signals to regulated responses at the level of different tissues, including muscle. These physiological processes within individuals can scale up to population responses to climate change. A mechanistic understanding of thermal responses is essential to predict the vulnerability of species and populations to climate change.